B(C6F5)(3): catalyst or initiator? insights from computational studies into surrogate silicon chemistry - Banerjee, Subhrashis; Vanka, Kumar (ACS Catalysis, 2018)
One of the most promising recent developments in catalysis has been the use of the metal-free Lewis acid B(C6F5)(3) as a catalyst for a range of different chemical transformations. Perhaps the most impressive achievement in this regard is the recently accomplished in situ generation of SiH4 from surrogates (Simonneau and Oestreich, Nat. Chem., 2015,7, 816). However, what the current computational work, with density functional theory, reveals is that this process, in addition to being catalyzed by B(C6F5)(3), is also significantly dominated by a series of autocatalytic reactions. The results are further corroborated by the use of the energetic span model, which shows that the turnover frequency is higher for the newly proposed autocatalytic pathway in comparison to the conventional B(C6F5)(3)-catalyzed pathway. The current work therefore provides interesting new insights into surrogate silicon chemistry. But, more importantly, the current studies indicate that B(C6F5)(3) is likely to function more as an initiator rather than a pure catalyst in many metal-free transformations that have been reported to date.
Keywords: autocatalysis; Density functional theory; ion-pair; Lewis acid catalysis; reaction mechanism; surrogate silicone chemistry; tris(pentafluorophenyl)borane